Income Shifting as Income Creation? The Intensive vs. the Extensive Shifting Margins - Håkan Selin; Laurent Simula (Center for Economic Studies and ifo Institute (CESifo), 2017)
The public finance literature has modeled income shifting as a decision along the intensive margin even though it involves significant fixed costs, giving rise to an important extensive margin. We show that accounting for this extensive margin has crucial policy implications: the classical distinction between income creation and income shifting breaks down. We make this point in a simple linear tax setting with a population of agents differing in terms of productivities, labor supply elasticities, and costs of income shifting. In the most empirically plausible scenario when people who shift easily are also more elastic in labor supply, giving them a lower tax rate is a good thing. This mechanism may be compared to third degree price discrimination in industrial organization. Numerical simulations suggest that fixed shifting costs have a large impact on optimal taxes. We further demonstrate that the conclusions derived for linear taxes carry over to non-linear tax schedules.
Keywords: H21; H24; 330; income shifting; optimal taxation; labor income tax